Exceptional smooth Bol loops - Larissa V. Sbitneva (International Journal of Mathematics and Mathematical Sciences)
One new class of smooth Bol loops, exceptional Bol loops, is introduced and studied. The approach to the Campbell-Hausdorff formula is outlined. Bol-Bruck loops and Moufang loops are exceptional which justifies our consideration.